Electrostimulation training effects on the physical performance of ice hockey players - Brocherie, F.; Babault, N.; Cometti, G.; Maffiuletti, N.; Chatard, J. C. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The aim of this study was to examine the influence of a short-term electromyostimulation (EMS) training program on the strength of knee extensors, skating, and vertical jump performance of a group of ice hockey players.